Violencia familiar y habilidades sociales en estudiantes de primaria del quinto ciclo de la Institución Educativa Rosa Agustina Donayre De Morey, Iquitos 2023 - Lopez Zavaleta, Juan Omar (2024)
The purpose of this study was to determine the relationship between family violence and social skills. It is a non-experimental, quantitative, cross-sectional, descriptive correlational study. The population consisted of 247 students in the fifth cycle of elementary school, and the sample was a census. The A, Goldtein & Col. family violence and social skills scale was used as an instrument for both variables, and surveys were used as a technique. Statistical graphs were used to analyze the averages and percentages of the data tables. Students in the sample perceived moderate family violence. The following conclusions were the most pertinent: By using Spearman's nonparametric Rho test The results showed that the hypothesis was valid, with p < 0.00. The information collected Rho = -, 606 allows us to observe that there is an inverse correlation: the greater the mistreatment, the lower the social skills in the fifth cycle students of the Rosa Agustina Donayre de Morey Primary Educational Institution. The study hypothesis that there is a statistically significant relationship between family violence and social skills was confirmed.